Hubungan Pola Asuh Permissive Terhadap Kenakalan Remaja di SMK Muhammadiyah 8 Banyuwangi - Putri, Millenia Zaskia; Ervina, Iin Dwi; Sari, Anggraeni Swastika (Jurnal Psikologi, 2024)
Support from the family is very important because it can influence the emergence of juvenile delinquency, because parental monitoring can determine the formation of behavior/character in children when they grow up. The aim of this research is to determine the relationship between permissive parenting patterns and juvenile delinquency at SMK Muhammadiyah 8 Banyuwangi. This research uses a correlational approach with quantitative methods. The subjects in this research were teenagers in classes X and the permissive parenting style scale uses a Likert scale with a validity value of 0.692 and a reliability of 0.900. The data analysis technique used is product moment. The results of the research show that there is a positive relationship between permissive parenting and juvenile delinquency at SMK Muhammadiyah 8 Banyuwangi with a correlation value of 0.553 with a significance level of 0.000. The relative contribution made by permissive parenting to juvenile delinquency is r²=0.306, of which permissive parenting contributes 30.6%, the rest is influenced by other factors.